Modelling Neonatal Care Pathways for Babies Born Preterm: An Application of Multistate Modelling - Seaton,SE; Barker,L; Draper,ES; Abrams,KR; Modi,N; Manktelow,BN (PLoS ONE, 2016)
Modelling length of stay in neonatal care is vital to inform service planning and the counsellingof parents. Preterm babies, at the highest risk of mortality, can have long stays in neonatalcare and require high resource use. Previous work has incorporated babies that dieinto length of stay estimates, but this still overlooks the levels of care required during theirstay. This work incorporates all babies, and the levels of care they require, into length ofstay estimates. Data were obtained from the National Neonatal Research Database for singletonbabies born at 24–31 weeks gestational age discharged from a neonatal unit inEngland from 2011 to 2014. A Cox multistate model, adjusted for gestational age, wasused to consider a baby’s two competing outcomes: death or discharge from neonatal care,whilst also considering the different levels of care required: intensive care; high dependencycare and special care. The probabilities of receiving each of the levels of care, orhaving died or been discharged from neonatal care are presented graphically overall andadjusted for gestational age. Stacked predicted probabilities produced for each week ofgestational age provide a useful tool for clinicians when counselling parents about length ofstay and for commissioners when considering allocation of resources. Multistate modellingprovides a useful method for describing the entire neonatal care pathway, where rates ofin-unit mortality can be high. For a healthcare service focussed on costs, it is important toconsider all babies that contribute towards workload, and the levels of care they require.